Late early Cretaceous adakitic granitoids and associated magnesian and potassium-rich mafic enclaves and dikes in the Tunchang–Fengmu area, Hainan Province (South China): Partial melting of lower crust and mantle, and magma hybridization - Wang, Q.; Li, X.; Jia, X.; Wyman, D.; Tang, G.; Li, Zheng-Xiang; Ma, L.; Yang, Y.; Jiang, Z.; Gou, G. (Elsevier Science BV, 2012)
This paper reports on a rare magmatic suite of adakitic rocks and associated magnesian and potassium-rich magmatic enclaves and dikes, which occur in the Tunchang–Fengmu area, Hainan Island (Southeast China). LA-ICP-MS zircon U–Pb age data show that they were generated in the late Early Cretaceous (~107 Ma). The adakitic rocks, consisting mainly of granodiorites and biotite granites, are high-K calcalkaline and have low Mg# values (0.27–0.50). They are geochemically similar to slab-derived adakites, e.g., with high SiO2, Al2O3, Sr, Sr/Y and La/Yb values, low Y and Yb contents, and negligible Eu and positive Sr anomalies. They also have relatively uniform (87Sr/86Sr)i (0.7086–0.7096), (206Pb/204Pb)i (18.50–18.61), (207Pb/204Pb)i (15.56–15.64) and (208Pb/204Pb)i (38.17–38.44) isotope ratios, with slightly variable εNd(t) (-3.85 to -6.55) and zircon in situ εHf(t) (-4.7 to +1.7) values. The mafic enclaves and dikes display disequilibrium textures (e.g., multiple-zoned clinopyroxene with low-MgO rims in contact with perthite and quartz microcrystals). They are high-K calc-alkaline and shoshonitic, and all but one sample have high Mg# (0.63–0.72) values. These mafic rocks are characterized by light rare earth element enrichment and heavy rare earth element (REE) depletion, negligible Eu and Sr and positive Pb anomalies, and Nb and Ta depletion. They have slightly more variable initial 87Sr/86Sr isotope ratios (0.7064–0.7086), εNd(t) (-5.1 to +0.1) values, and (206Pb/204Pb)i (18.35–18.50), (207Pb/204Pb)i (15.45–15.59) and (208Pb/204Pb)i (38.18–38.70) ratios.One mafic dike sample has zircon in situ εHf(t) values (-4.94 to -2.42) similar to those of adakitic rocks (-4.7 to +1.7) in the area. We suggest that the adakitic rocks were most likely generated by partial melting of newly underplated basaltic lower crust with arc-like geochemical characteristics, and the primitive compositions of the mafic enclaves and dikes likely originated from lithospheric + asthenospheric mantle sources metasomatized by subducted oceanic sediments or a relatively juvenile lithospheric mantle source. Mantle-derived primitive magmas likely underwent mixing at depth with minor crustally-derived felsic magmas before being injected into the adakiticmagma chamber. Such injections may have broken up the magma into discrete globules and convective motion distributed the enclaves through the adakitic host. Asthenosphere upwelling due to the roll-back of the subducted Paleo-Pacific plate likely triggered the coeval late Early Cretaceous crust- and mantle-derived magmatism, resulting in the magma hybridization observed on Hainan Island.